FLAT PLATE PULSATING HEAT PIPES WITH DIFFERENT CHANNEL GEOMETRIES FOR HIGH HEAT FLUX APPLICATIONS - Krambeck, L.; Domiciano, K. G.; Betancur-Arboleda, L. A.; Mantelli, M. B. H. (Revista de Engenharia Térmica, 2021)
The thermal performance of flat plate pulsating heat pipes with different channel geometries was performed in this experimental work. The tests were accomplished with two channel profiles, round and grooved. One of the channel geometries, located on the evaporator, can be considered novel, consisting of a round channel with two lateral grooves. Diffusion bonding technology was used to manufacture the PHPs made of two copper flat plates. Distilled water was used as the working fluid with a filling ratio of 50% (17.9 ml) of the total volume. The pulsating heat pipes were tested at one position (vertical) under heat loads from 20 up to 2000 W. The experimental results showed that both flat plate pulsating heat pipes operates successfully for high heat fluxes. The lateral grooves reduced the thermal resistance, being principally efficient in lower loads. Besides that, the novel channel considerably anticipated the operation startup. Therefore, a much better performance was obtained by the grooved channel PHP, which was constructed from a simple, low cost modification of the fabrication process.